2021
DOI: 10.1051/e3sconf/202124903012
|View full text |Cite
|
Sign up to set email alerts
|

DNA sexing for gender determination of Changeable Hawk-Eagle (Nisaetus cirrhatus, Gmelin, 1788)

Abstract: The Changeable hawk-eagle (Brontok eagle) is a protected bird species. It is one of the most frequently hunted and traded birds in Indonesia. The processes of being traded changes this bird natural behaviour. Therefore, a rehabilitation effort to return the eagle’s behaviour to conform to its natural habits is needed. The ultimate goal of rehabilitation is to release the changeable hawk-eagle back into its natural habitat. In conservation and breeding programs, efforts to determine the sex of eagles to be rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
(17 reference statements)
0
2
1
Order By: Relevance
“…In a recent study, it was reported that the length of CHD1-Z in DNA sexing of N. bartelsi and N. cirrhatus ranged from 640 to 758 bp (N. bartelsi) and 690 to 758 bp (N. cirrhatus). Another study reported that the length of CHD1-Z in N. cirrhatus and B. liventer ranged from 638-725 bp (N. cirrhatus) and 600-700 only (B. liventer) (Sitohang 2017;Annisa et al 2021;Kaewhom and Srikijkasemwat 2021). It can be interpreted that the results of PCR products obtained from this study were not significantly different from previous studies that conducted molecular sexing in raptors.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…In a recent study, it was reported that the length of CHD1-Z in DNA sexing of N. bartelsi and N. cirrhatus ranged from 640 to 758 bp (N. bartelsi) and 690 to 758 bp (N. cirrhatus). Another study reported that the length of CHD1-Z in N. cirrhatus and B. liventer ranged from 638-725 bp (N. cirrhatus) and 600-700 only (B. liventer) (Sitohang 2017;Annisa et al 2021;Kaewhom and Srikijkasemwat 2021). It can be interpreted that the results of PCR products obtained from this study were not significantly different from previous studies that conducted molecular sexing in raptors.…”
Section: Discussioncontrasting
confidence: 59%
“…More males will affect social behavior, mainly caused by male aggression, leading to competition with other males. In addition, the sex ratio imbalance can impact population density and growth rates, demographic problems, and, worst-case scenario, extinction (Annisa et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from brief records on its predation habits (Fam andNijman 2011, Najmuddin et al 2019), information on the species' behavior in Malaysia is limited to basic biology (Ferguson-Lees andChristie 2001, Wells 2007a). Elsewhere, studies have been conducted covering its nesting ecology (Gokula 2000, Gunawan et al 2017, Senanayake et al 2017, Aldy and Zainun 2019, Sentanu et al 2019, Rodrigues et al 2020, Boer et al 2021, predation habits (Gokula 2000, Sirdesai et al 2013, Pierce et al 2014, home-range (Widiana et al 2017, Gunawan et al 2021), habitat selection (Nijman 2004), distribution (Rodrigues et al 2020), vocalization (Gjershaug et al 2020), genetics (Zein 2018, Pharmawati and Yuni 2020, Krisdayana et al 2021, phylogeny (Haring et al 2007, Rifaldo et al 2020, sex determination (Annisa et al 2021), and gastrointestinal infection (Kurniawan et al 2010).…”
Section: Introductionmentioning
confidence: 99%